2004
DOI: 10.1016/s1476-5586(04)80054-x
|View full text |Cite
|
Sign up to set email alerts
|

L-Type Amino Acid Transporter-1 Overexpression and Melphalan Sensitivity in Barrett's Adenocarcinoma

Abstract: The L-type amino acid transporter-1 (LAT-1) has been associated with tumor growth. Using cDNA microarrays, overexpression of LAT-1 was found in 87.5% (7/8) of esophageal adenocarcinomas relative to 12 Barrett's samples (33% metaplasia and 66% dysplasia) and was confirmed in 100% (28/28) of Barrett's adenocarcinomas by quantitative reverse transcription polymerase chain reaction. Immunohistochemistry revealed LAT-1 staining in 37.5% (24/64) of esophageal adenocarcinomas on tissue microarray. LAT-1 also transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 38 publications
0
50
0
1
Order By: Relevance
“…Tissue slices were incubated with BPA 1 hour after exposure and removal of tyrosine (25), 10 minutes after BCH (without removal; refs. 24,26), and simultaneously with phenylalanine for the time periods shown in Fig. 5, after which they were washed and analyzed for boron content.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissue slices were incubated with BPA 1 hour after exposure and removal of tyrosine (25), 10 minutes after BCH (without removal; refs. 24,26), and simultaneously with phenylalanine for the time periods shown in Fig. 5, after which they were washed and analyzed for boron content.…”
Section: Resultsmentioning
confidence: 99%
“…Up-regulation of LAT-1 thus seems to be a common feature of tumor cells and of interest in targeting treatments dependent on LAT-1 function, such as transported cytotoxic drugs (e.g., melphalan; ref. 26) or enhancement of BNCT by increased uptake of boron using BPA. Clinical evidence of the role of LAT-1 has been implied by Langen and colleagues and Kuwert and colleagues in studies (14,15) that showed increased tracer (IMT) concentration in progressively more active tumors, suggesting a link between tracer uptake (L-amino acid handling) and proliferative activity and, at the same time, calling into question the use of the LAT-1/ BPA system for BNCT treatment of malignant tumors where the proliferation rate in vivo has been shown to be low (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…In view of the evaluation of LAT1 substrates and inhibitors as potential anticancer drugs (36)(37)(38), 18 F-L-FEHTP is a candidate PET tracer for staging tumors according to their LAT1 expression and activity and therefore their susceptibility to LAT1-targeted drugs. In addition, the in vivo efficiency of LAT1 inhibitors may be monitored directly by PET.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of mRNA Using Oligonucleotide Arrays-For correlation of protein and RNA gene expression patterns, a range of non-dysplastic and dysplastic Barrett samples and esophageal adenocarcinomas were examined by high density oligonucleotide microarrays as described previously (11,12). We compared mRNA expression of 46 samples, including nine Barrett metaplasia, seven samples with a mixture of Barrett metaplasia and low grade dysplasia, eight low grade dysplasia, seven high grade dysplasia, and 15 esophageal adenocarcinomas.…”
Section: Methodsmentioning
confidence: 99%